Epistemology - An Islamic perspective - Azram, Mohammad (IIUM Press, 2011)
Since man is the vicegerent of God in this world. And in order to enable him to fulfill his responsibilities (of his vicegerency), God has endowed man with the potentials of creative & conceptual knowledge. It becomes incumbent upon him to mould knowledge in the framework provided by Islam. Thus all types of knowledge whether it is Natural Science, Social Science or even Pure Science, should be understood with the aim to establish an Islamic System. In this paper we will discuss the background of epistemology, different areas of epistemology-like source, types (revealed and derived), elements in Islam, principles (Unity of Allah, unity of creation,and unity of thoughts) and limitations.